Anticancer, Antioxidant, Antimicrobial Activities, and HPLC Analysis of Alcoholic Extracts of Parthenocissus quinquefolia L. Plant Collected from Çanakkale - Sevil Kalın; Ersin Karabacak; Pınar Ilgın; Alper Önder; Özlem Maraba; Ferah Cömert Önder (Journal of Advanced Research in Natural and Applied Sciences)
This study aimed to contribute to revealing the health effects of the Parthenocissus quinquefolia L. (PQ) plant by examining the biological activities of various extracts of the plant. An ethnobotanical important medicinal plant, PQ belongs to the Vine family (Vitaceae) and is known for its medicinal uses. Herein, fruit and leaf alcoholic extracts of the plant exhibited anticancer activity on triple negative breast cancer (TNBC) cell lines, estrogen receptor positive (ER+) (MCF-7), and human colon adenocarcinoma (HT-29) cancer cell lines. Furthermore, fruit methanol extracts displayed strong radical scavenging activity with low IC50 values such as 0.51 mg/mL, 0.80 mg/mL, 0.84 mg/mL, and 1.45 mg/mL. The highest TEAC values (18.72 mM Trolox/mg, 9.90 mM Trolox/mg, and 8.41 mM Trolox/mg) were calculated for the extracts of red leaves. The antifungal activity was determined against Candida albicans as fungal pathogen. The cell apoptosis with methanol extract was obtained between 20 µg/mL and 70 µg/mL for 48 h and 72 h treatments by Hoechst 33258 staining of nuclei under a fluorescence microscopy. HPLC analysis was performed for methanol extracts to determine major bioactive components. Consequently, this plant extracts may guide to new strategies and may be uses in medicinal applications for further investigations.